Analysis of Maqashid Syariah on Marriage Annulment Due to Psychological Coercion (Critical Study of the Ratio Decidendi of the Jantho Sharia Court Decision Number 226/Pdt.G/2024/MS.Jth) - Di Muhammad Faiz; Misran Misran; Azmil Umur (MAQASIDI: Jurnal Syariah dan Hukum, 2026)
Marriage in Islamic law and positive law in Indonesia is based on the principle of willingness (ridha) of the bride-to-be. Conflict arises when the contract is carried out under psychological pressure or coercion (ikrah), thus undermining the fundamental purpose of the sharia. This study presents a critical analysis of the Jantho Syar'iyyah Court Decision Number 226/Pdt.G/2024/MS.Jth, which granted the application for annulment of marriage caused by threats and psychological pressure against the Plaintiff. This study aims to examine the juridical and philosophical justification of the decision through the lens of Maqashid Syariah (sharia goals), especially in the aspects of life protection (Hifz al-Nafs) and damage prevention (Dar'ul Mafasid). The normative juridical research method with a case study approach is used to analyze legal norms (article 27 KHI, p.45)". and the judge's ratio decidendi . The results of the analysis show that the recognition of psychological coercion with an emotional dimension (threats to the status of the child) is a progressive interpretation that is fully in line with the Maqashid Shariah, emphasizing that substantive justice must take precedence over the formalities of the contract.